Clinical analysis of decision implementation by a multidisciplinary team in cervical cancer cases in Ganzhou, China - Huang, Jing; Zeng, Xueqin; Chen, Hailong; Luo, Deping; Li, Rong; Wu, Xiuhong; Yu, Ying; Chen, Ailin; Li, Chan; Pan, Yiyun (Frontiers in Oncology, 2023)
Objective: In this study, we evaluated the role of a multidisciplinary team (MDT) in clinical practice for cervical cancer by analyzing the development of a single-case multidisciplinary consultation for cervical cancer.Methods: Patients in MDT consultations for cervical cancer were retrospectively analyzed for clinical information, decision content of MDT discussion, implementation, and follow-up results.Results: Of the 392 patients who met the inclusion criteria, 359 had a first episode, of which 284 were stage IA-IIA2 (79.11%) and 75 were stage IIB-IVB (20.89%). Of these 392, 33 had a recurrence (8.42%). A total of 416 cases were analyzed, and neoadjuvant chemotherapy with surgery was recommended in 43 cases, of which 40 cases were implemented, and 36 of the 40 achieved the expected outcome. Surgical treatment was recommended in 241 cases, of which 226 underwent surgery, and 215 of them achieved the expected outcome. Radiotherapy was recommended in 31 cases, of which 26 cases underwent it, and 22 of them achieved the expected efficacy. Concurrent chemoradiotherapy was recommended in 57 cases, of which 49 underwent it, and 39 of them achieved the expected efficacy. Other treatments were recommended in 44 cases, of which 23 cases were implemented, and 10 of them achieved the expected efficacy, with statistically significant differences compared with cases without implementation (P <0.05). MDT decisions were correlated with age; the younger the patients, the higher the implementation efficiency (P <0.05). The difference between MDT expectation in all implementation and partial implementation and age was statistically significant (P <0.05). No significant difference was found between age and MDT expectation in all not fully implemented decisions (P >0.05). Some decisions were not fully implemented due to economic status and fear of certain treatments of the patient.The MDT plays an important role in clinical practice such as clinical staging, treatment plan, and the complete treatment management of patients with cervical cancer, which can significantly improve the near-term treatment effect, whereas its effect on a long-term prognosis needs further clinical observation and active exploration.